Polarization-Resolved Raman Study of Bulk-like and Davydov-Induced Vibrational Modes of Exfoliated Black Phosphorus - Phaneuf-L’Heureux, Anne-Laurence; Favron, Alexandre; Germain, Jean-Francis; Lavoie, Patrick; Desjardins, Patrick; Leonelli, Richard; Martel, Richard; Francoeur, Sebastien (Nano letters, 2016)
Owing to its crystallographic structure, black phosphorus is one of the few 2D materials expressing strongly anisotropic optical, transport, and mechanical properties. We report on the anisotropy of electron–phonon interactions through a polarization-resolved Raman study of the four vibrational modes of atomically thin black phosphorus (2D phosphane): the three bulk-like modes A g 1, B 2g , and A g 2 and the Davydov-induced mode labeled A g (B 2u ). The complex Raman tensor elements reveal that the relative variation in permittivity of all Ag modes is irrespective of the atomic motion involved lowest along the zigzag direction, the basal anisotropy of these variations is most pronounced for A g 2 and A g (B 2u ), and interlayer interactions in multilayer samples lead to reduced anisotropy. The bulk-forbidden A g (B 2u ) mode appears for n ≥ 2 and quickly subsides in thicker layers. It is assigned to a Davydov-induced IR to Raman conversion of the bulk IR mode B 2u and exhibits characteristics similar to A g 2. Although this mode is expected to be weak, an electronic resonance significantly enhances its Raman efficiency such that it becomes a dominant mode in the spectrum of bilayer 2D phosphane.